PEMBINAAN KOMPETENSI SOSIAL GURU PKN PASCA SERTIFIKASI DI KOTA SEMARANG - Intani, Ranja Dwi (Unnes Civic Education Journal, 2015)
The Minister Decree no 16 Year 2007 regulates that every teacher must meet the national standards of academic qualifications and competence of teachers. To realize this vision of Semarang City Department of Education held a Fostering Social Competence Civics Teacher Certification After the background is still low in terms of the attitude of a teacher interact / communicate with people outside the school. Formulation of the problem in this study were 1) how the condition of social competence post Civics teacher certification in the city of Semarang and 2) how the development of social competence post Civics teacher certification in the city of Semarang. The results suggest that social competence post Civics teacher certification in the city of Semarang as a whole has been good (82% post-certified Civics teachers have mastered the social competence and 18% post-certification Civics teachers have not mastered the social competence). Coaching to improve the quality of social competence of post certified civics teacher are through short-term training programs such as workshops, and seminars, and long-term program such as teaching clinic and MGMP (Subject Teacher Council). Programs still planned are PKG (Teacher performance Appraisal) and PKB (professionalism Sustainable development).